Kolonialisme dan Dikotomi Pendidikan di Indonesia - Putra Daulay, Haidar; Dahlan, Zaini; Priono, Andika; Lubis, Asrul Parlindungan (Medan Resource Center, 2021)
It is well known that Indonesia is a vast area and is very rich with various natural resources, including spices. These spices became the initial attraction for European nations to come to Indonesia, because they really needed them. The arrival of European nations (especially the Portuguese, Dutch and British) since the 9/15 century to trade which later developed into political and military colonization. The Dutch colonial occupation had very complex motives and goals with three major themes, which were often referred to as 3G: Gold (Gold), Glory (Power), and Gospel (Religion / Gospel), namely Economy, politics and religion. In relation to these interests, the drafters of the concept of education seemed unable to separate themselves from the socio-economic and political conditions of the Dutch central government, and their relation to the political interests of the Dutch East Indies. Thus every policy implemented in the field of education tended to be related to the interests of Dutch colonial politics in Indonesia. So that Islamic education itself is difficult to develop and its development is very limited and not given free space.